A chemical space odyssey of inhibitors of histone deacetylases and bromodomains. Issue 61 (13th June 2016) - Prieto-Martínez, Fernando D.; Gortari, Eli Fernández-de; Méndez-Lucio, Oscar; Medina-Franco, José L.
Abstract : The interest in epigenetic drug and probe discovery is growing as reflected in the large amount of structure-epigenetic activity information available. Abstract : The interest in epigenetic drug and probe discovery is growing as reflected in the large amount of structure-epigenetic activity information available. Therefore, the significance of understanding the entire or fractions of the epigenetic relevant chemical space is increasing. Major epigenetic targets are histone lysine deacetylases (HDACs), bromodomains (BRDs), and DNA methyltransferases (DNMTs). However, with the exception of DNMTs, characterization of the chemical space of these epi-targets is limited. This work is the first chemoinformatic analysis of the physicochemical properties, structural diversity, and coverage of the chemical space of compounds screened as inhibitors of HDACs and BRDs. The chemical space was compared to DNMTis, approved drugs, commercial screening compounds, and generally recognized as safe (GRAS) molecules. The structural complexity of compounds directed towards epigenetic targets was also addressed. The outcome of this analysis indicated that it is required to increase the structural diversity and molecular complexity of screening libraries tested as modulators of DNMTs, HDACs and BRDs. Results also suggested that it is feasible to develop dual inhibitors targeting HDACS and BRDs. This work has implications in repurposing of food chemicals with potential epigenetic activity and design of poly-epigenetic compounds.